Two-balloon epistaxis catheter to ensure vaginal patency in a complex case of vaginoplasty for vaginal agenesis: a case report - Chiara Costantini; Federica Fati; Elisa Pani; Fabio Beretta; Silvia Bisoffi; Giosuè Mazzero; Elisa Negri; Clara Revetria; Hamid R. Sadri; Enrico Ciardini (PAGEPress Publications, 2023)
Congenital vaginal atresia is a rare anomaly of the female genital tract. Many vaginoplasty procedures have been described, but the postoperative risk of vaginal stenosis remains a challenge. We report a case of isolated distal vaginal agenesis in a patient with neurological impairment where the use of an "alternative" dilator was needed. An 11-year-old girl with Down syndrome was admitted to the Emergency Department complaining of pelvic pain. The clinical evaluation showed a hard and painful pelvic mass associated with an imperforate hymen. Abdominal ultrasound and pelvic MRI were suggestive for hematometrocolpos and absence of the lower third segment of the vagina. Vaginoscopy confirmed the diagnosis of congenital vaginal agenesis. The patient then underwent a laparoscopic-assisted vaginoplasty. Considering the difficult management of the postoperative period, an epistaxis catheter was used as a vaginal stent and dilator. The use of an epistaxis catheter to provide adequate vaginal patency after vaginoplasty can be an alternative solution especially in those cases where calibrations with dilators are difficult or not tolerated.